Customer stimulation in lean software development - Linden, Iiro (fi=Turun yliopisto|en=University of Turku|, 2016)
The process of developing software is a complex undertaking involving multiple stakeholders. While the intentions of these parties might vary to some extent, the ultimate goal can be seen as a satisfactory product. Lean and agile software development practices strive toward this and they place customer contentment as one of the highest aims of the process. An important aspect of any development process is the act of innovation. Without it, nothing progresses and the whole process is unnecessary. As a target domain expert, the customer is an important part of effective innovation. Problems arise, however, when the customer is not actively taking part in the activities. Lack of familiarity with software development can easily cause such issues. Unfortunately, the amount of research conducted on product innovation is unimpressive. This makes it difficult to formulate a recommended approach on stimulating the customer and encouraging a more active participation. Ultimately, a small set of high-level guidelines were identified from the available literary resources for inducing innovation. To conclude, this thesis presents the findings made during the development of a small web application and compares them to the aforementioned literature findings. While the guidelines seem to provide promising results, further empirical research is needed to attain more significant conclusions.
Asiakkaan stimulointi lean-ohjelmistokehityksessa